Development of a high throughput methodology to screen cathinones' toxicological impact. (May 2019) - Ferreira, Carla; Vaz, Ana Rita; Florindo, Pedro R.; Lopes, Álvaro; Brites, Dora; Quintas, Alexandre
Highlights: It is difficult to characterize synthetic cathinones toxicological profiles on an acceptable time scale using animal models or human cells. The yeast Saccharomyces cerevisiae has been proven an invaluable model organism to study the fundamental toxicological molecular mechanisms. High throughput methodology developed to screen cathinones' toxicological impact using S. cerevisiae . S. cerevisiae in the presence of synthetic cathinones was able to detect the most toxic substances. This screening tool methodology is useful to prioritize the most toxics NPS in early warning programs. Abstract: Current trend of novel psychoactive substances (NPS) among teenagers is posing new clinical, scientific and forensic societal questions. Synthetic cathinones are among the most consumed groups of NPS appearing on the street market and internet on a regular basis. The properties of these substances change regularly, due to structural modification to circumvent legislation. This practice makes almost impossible to characterize its toxicological profiles on an acceptable time scale, mostly due to the time-consuming experiments that must be held in animal models or human cells by standard methods. Such an issue demands the development of a rapid and inexpensive methodology to be used as a high-throughput screening of cathinones' toxicity. The yeast Saccharomyces cerevisiae shares highly conserved molecular and cellular mechanisms with human cells and has been used before for pharmacological drugs. In the present work it is proposed to use S. cerevisiae growth curves as a high throughput screening method to profile synthetic cathinones toxicity in a short time scale. The results obtained by S. cerevisiae growth curves analysis were compared to differentiated SH-SY5Y human neuronal cells and similar responses were found. The screening tool methodology has shown able to prioritize the most toxics NPS and can be useful for early warning programs on NPS.